The Business Judgment Rule Limiting State-Owned Enterprise Directors’ Liability After the SOE Law Amendment - fareh prameswari; Syofyan Hadi (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the function of the Business Judgment Rule (BJR) as a boundary of legal liability for the management organs of State-Owned Enterprises (SOEs) in Indonesia following the recent amendments to the State-Owned Enterprises Law. Using a normative juridical research method with statutory and conceptual approaches, this research analyzes the normative foundation of BJR within Indonesian corporate law, the implications of regulatory changes on the responsibilities of directors, commissioners, and supervisory boards, and the extent to which BJR can serve as a shield against civil and criminal liability. The findings show that BJR, grounded in fiduciary duties under the Limited Liability Company Law, provides legal protection for business decisions made in good faith, without conflicts of interest, based on adequate information, and within the scope of authority. However, the removal of the provision excluding SOE organs from the category of state officials has widened potential liability and necessitated greater professional accountability. The study further reveals differences in the application of BJR between Persero-type SOEs, which are fully governed by private corporate law, and Perum-type SOEs, which remain tied to public administrative principles, creating risks of disharmony with anti-corruption and state finance laws. The research concludes that the ideal model for implementing BJR in SOEs requires standardized risk assessment procedures, strengthened oversight documentation, and harmonization of the SOE Law, Company Law, Anti-Corruption Law, and State Finance Law to ensure a balance between managerial protection and state accountability in managing public assets.